Penerapan Teknologi Realitas Virtual untuk Pelatihan Keselamatan Pekerja dalam Operasi Mesin Industri Berat - Effendi, Ryan; Zulfikar, Iwan; Rusba, Komeyni; Kartika, Siska Ayu; Utama, Satrio Darma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The application of Virtual Reality (VR) technology in worker safety training in heavy industries has been an intriguing subject of research in recent years. This journal article aims to provide a literature review on how VR is utilized in this context. The literature review method is employed to gather, evaluate, and synthesize findings from various related studies. This literature review reveals that the use of VR has proven effective in enhancing worker safety and operational skills in various heavy industries. By enabling training in a simulated virtual environment, VR technology can deliver realistic experiences without actual physical risks. Previous studies indicate that workers who receive VR training tend to have a better understanding of potential risks and safety procedures, leading to a decrease in accident rates. The advantages of VR also include its ability to provide repeatable training without significant additional costs. This allows workers to gain consistent hands-on experience, reinforcing their skills in hazardous situations. Thus, the use of VR in worker safety training in heavy industries promises significant benefits in efforts to improve worker safety and well-being.